Physicochemical Properties of Dangke Nuggets with the Addition of Corn Flour (Zea Mays L.) - Nurjannah, Siti; Malaka, Ratmawati; Nahariah, Nahariah (Hasanuddin Journal of Animal Science (HAJAS), 2024)
This study aimed to analyze the effect of dangke nuggets with the addition of corn flour on the physicochemical properties of dangke nuggets. This study used a completely randomized design (CRD) factorial pattern with three replications and three treatments. The first factor was corn flour addition level of 0%, 5%, and 10%, and the second factor was storage time of 0, 14, and 28 days in the freezer. Physicochemical testing included the Cooking Loss test, nugget breakability, water content, protein content, and fiber content. The results showed a correlation between the corn flour addition level and the storage time, which had a significant effect (P<0.01) on the Cooking Loss, water content, protein content, and fiber content of dangke nuggets. At the same time, there was no correlation between the corn flour addition level and the storage time for shear force, which had no significant effect (P>0.05). Based on the study, it can be concluded that the addition of 5% corn flour to the formulation can increase protein content. In comparison, adding 10% corn flour provides the best quality in terms of cooking loss, nugget-breaking power, and water content and increases the fiber content of the nugget. The longer the storage, the lower the water content and protein content, reducing the quality of cooking loss and nugget-breaking power. Keywords: Dangke, nuggets, corn flour, physicochemical properties